PENGARUH LITERASI KEUANGAN, MOTIVASI, RELIGIUSITAS DAN PERSEPSI KEMUDAHAN TERHADAP MINAT BERINVESTASI GENERASI Z PADA REKSADANA SYARIAH DI JABODETABEK - RIFA AWALIYAH RAHMI (2021)
Generation Z is expected to be a long-term investment segment by OJK. Even though they have started investing, most of Generation Z still feel they are limited to basic knowledge and they feel they need more knowledge about investing.The purpose of this study was to determine the effect of financial literacy, motivation, religiosity and perceived ease of investment on generation Z's interest in investing in Islamic mutual funds. The quantitative approach is the research method chosen to carry out this research. The sample used is generation Z who is in the Jabodetabek area and has an understanding of sharia mutual funds. The use of thescale is Likert used in the questionnaire to obtain data. This study uses multiple linear regression analysis which is supported by validity and reliability tests, classical assumption tests, and hypothesis testing consisting of the F test, T test, and determination coefficient test assisted by SPSS version 25 software The results of this study show that simultaneously financial literacy, motivation, religiosity, and perceived convenience have a significant effect on the interest in investing in Generation Z in sharia mutual funds in Jabodetabek. While partially financial literacy, motivation, and perceived convenience variables have a significant effect on the variable of interest in investing in Generation Z in sharia mutual funds in Jabodetabek, but the religiosity variable has no effect.